Seasonal and spatial comparisons of microzooplankton grazing and phytoplankton growth in the Bohai Bay, China - Wen, Yujian; Zhang, Guodong; Song, Yuyao; Zhang, Guicheng; Sun, Jun (Frontiers in Marine Science, 2023)
The dilution experiment technique was used in two cruises in July-August (summer) and October-November (autumn) 2020, with a total of 14 stations. The grazing impact of microzooplankton on phytoplankton in the interior of Bohai Bay was comprehensively investigated. We compared phytoplankton growth rates (0) and microzooplankton grazing rates (m) spatially (distance between experimental stations and shore far vs. near) and seasonally (summer vs. autumn). Both m and 0 values were significantly higher in summer than in autumn, and the phytoplankton growth rate 0 was positively correlated to temperature. Offshore stations showed higher values. There is no significant spatial and seasonal differences in the ratio of microzooplankton grazing rate and phytoplankton growth rate (m/0) indicating that daily consumption of primary production by microzooplankton was similar in the two seasons. Therefore, our research showed a close coupling between microzooplankton grazing with phytoplankton growth in the Bohai Bay.